Analisis Model Bisnis dan Nilai Tambah Produk Hasil Olahan Ikan di UMKM Torani Sumber Makmur, Kota Cirebon - Siti Nurhasanah; Atikah Nurhayati; Roffi Grandiosa Herman; Ine Maulina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the business model applied by UMKM Torani Sumber Makmur through the Business Model Canvas approach and analyze the added value of processed fish products at UMKM Torani Sumber Makmur. This research has been conducted at UMKM Torani Sumber Makmur, Cirebon City in August 2024 - April 2025. The research method used is a case study method with a quantitative and qualitative approach. Data collection was carried out by observation, interviews, questionnaires, and documentation. The sampling method used was purposive sampling, and the snowball sampling method. Data analysis used is business model canvas analysis and added value. The research results from the business model canvas analysis show that the application of the business model at UMKM Torani Sumber Makmur can contribute to the success of the business being run. The results of the added value analysis show that processed fish products at UMKM Torani Sumber Makmur have added value with the highest added value being ekado products amounting to Rp.219,025 / kg with a percentage ratio of added value to product value of 78.22%. Fish roll products amounted to Rp.135,194 / kg with a percentage ratio of added value to product value of 72.82%. Salmon fish dumplings products amounted to Rp.112,227 / kg with a percentage ratio of added value to product value of 53.44%. Salmon fish meatball products amounted to Rp.88,717 / kg with a percentage ratio of added value to product value of 47.96%